Online Assessments: Their Importance in Higher Education - Karunarathne, G. D. D. T.; Wijewardene, L. (Advances in Social Sciences Research Journal, 2021)
The main purpose of this review article is to deliberate on online assessments, the advantages and disadvantages of e-assessments, and their importance in the higher education sector, in the post-COVID era. Online assessments are the collection of tasks that are made by educational instructors in order to evaluate student performance, using Information and Communication Technologies. There are different types of techniques to conduct e-assessments, which result in different rewards and shortcomings. However, this article delivers the strategies that can be used to eliminate the downsides of online assessment.